Acute myocarditis according to age: Presentation, management and early outcomes - Clément Karsenty; Paul Vignaud; Clara Brusq; Pamela Moceri; Pascal Lim; Edouard Gerbaud; Olivier Lairez; Coline Lelarge; Caroline Ovaert; Claire Bouleti; Oscar Werner; Vanina Bongard; et al. (ESC Heart Failure, 2025)
Abstract Aims Acute myocarditis (AM) is a rare but severe disease affecting patients of all ages. Large multicentric studies comparing children and adults are currently lacking. We aimed to elucidate differences in presentation, management, and outcomes of AM across age groups. Methods We analysed a comprehensive French national cohort study, encompassing 53 paediatric and adult units from March 2020 to November 2021, collecting data on baseline characteristics, evolution, management and in‐hospital complications. Myocarditis‐related events (MRE) within 30 days included all‐cause death, cardiogenic shock, cardiac arrest, ventricular arrhythmias or complete AV block. Results We included 745 AM patients (328 children and 417 adults), mainly male (73.4%) with a median age of 10.9 years [Q1–Q3 (7.3–14.6)] for children and 28.7 years [22.6–41.2] for adults. Multisystem inflammatory syndrome (MIS) was more prevalent among children (69.8%), and infectious aetiologies dominated in adults (13.4 vs. 52.4%). Children exhibited more severe clinical presentation (15.9 vs. 7.2%, P < 0.001, with heart failure and 14.4 vs. 6.9%, P < 0.001, with cardiogenic shock), requiring higher use of inotropes (25.0 vs. 9.4%, P < 0.001), vasopressors (12.0 vs. 6.2%, P < 0.001), and ventilatory support (13.7% vs. 7.9%, P = 0.01). Cardiac treatments were used less frequently in children, and corticosteroids (68.3 vs, 14.3, P < 0.001) and immunomodulators (65.1 vs. 4.5%, P < 0.001) were more common. MRE occurrence was substantial but not significantly different between children and adults (18.1 vs. 13.4%, P = 0.09). Extra‐cardiac manifestations at admission were significant predictors of MRE [adjusted odds ratio 2.40 (1.43–4.38)], regardless of MIS status. Conclusions AM exhibits variations in presentation, aetiologies and management but has a comparable 30 day prognosis in children and adults. These findings underscore the importance of tailored management strategies in AM across different age groups.